Relationship between anxiety levels and dyspnea among post-COVID-19 patients - Ali Multazam; Diah Nur Pratiwi; Nurul Aini Rahmawati (Physical Therapy Journal of Indonesia, 2023)
Background: Post-corona-virus disease 2019 (Post-COVID-19) syndrome also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a condition where symptoms arise in COVID-19 patients who have been declared cured according to negative swab results. The level of anxiety can cause it because when anxiety occurs, there is a "fight or flight" response to protect oneself. The sympathetic nervous system works and releases the adrenaline hormone, causing dyspnea. Research objective knowing the relationship between anxiety levels and dyspnea in post-COVID-19 patients in Malang Raya. Methods: This study used a cross-sectional design. The population of this study consisted of post-COVID-19 patients who live in Malang Raya, with a sample of 56 respondents. This study collected data of the Hamilton rating scale for anxiety (HRS-A) questionnaire to measure the level of anxiety and the Borg Scale to measure the level of dyspnea. Results: Based on Spearman's statistical test, the level of anxiety and dyspnea obtained a value of p= 0.00, r= 0.503 with quite strong results, so there is a relationship between the level of anxiety and dyspnea. Conclusion: There was a strong relationship between the level of anxiety and dyspnea in post-COVID-19 patients.